2022
DOI: 10.4168/aair.2022.14.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Mucus Plugs and Small Airway Dysfunction in Asthma, COPD, and Asthma-COPD Overlap

Abstract: Purpose There are reports concerning mucus plugs detected on high-resolution computed tomography images and airflow obstruction in asthma and chronic obstructive pulmonary disease (COPD). However, little is known about the associations between mucus plugs and small airway dysfunction (SAD). We evaluated the relationship between mucus plugs and pulmonary function in patients with asthma, COPD, and asthma-COPD overlap (ACO), and investigated the relevance to SAD and type 2 inflammation in a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
4
15
0
Order By: Relevance
“…12 It was previously demonstrated that asthma patients with higher MPS have significantly elevated sputum eosinophils, gene expression of IL13 and IL5, and MUC5AC/MUC5B ratios. 4 This explains our findings in this study that asthma patients with MPs exhibit higher levels of routinely measured T2 biomarkers in real-life clinical practice, including blood eosinophils, FeNO, 5 and total IgE, 10 in which median values in the MP group all exceeded traditionally accepted cut points of 300 cells/ mL or greater, 25 parts per billion or greater, and 100 kU/L or greater, respectively. Furthermore, despite the suppressive effect of ICS on FeNO, 13 patients with MPs were receiving a significantly higher ICS dose but still had higher FeNO levels.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…12 It was previously demonstrated that asthma patients with higher MPS have significantly elevated sputum eosinophils, gene expression of IL13 and IL5, and MUC5AC/MUC5B ratios. 4 This explains our findings in this study that asthma patients with MPs exhibit higher levels of routinely measured T2 biomarkers in real-life clinical practice, including blood eosinophils, FeNO, 5 and total IgE, 10 in which median values in the MP group all exceeded traditionally accepted cut points of 300 cells/ mL or greater, 25 parts per billion or greater, and 100 kU/L or greater, respectively. Furthermore, despite the suppressive effect of ICS on FeNO, 13 patients with MPs were receiving a significantly higher ICS dose but still had higher FeNO levels.…”
Section: Discussionsupporting
confidence: 56%
“…The mean (95% CI) difference of 0.80 L/s (0.44-1.17 L/s) aligns with a recent study. 10 Mucus plugging is thought to be driven by IL4/IL13mediated inflammation. 3 Thus, we postulate that this is a potential mechanism by which the anti-IL4ra dupilumab may improve FEV 1 and FEF 25-75 in severe asthma by reducing mucin and tissue eosinophils in addition to having a direct effect on airway smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…of Studies Reference No. Lower Upper I 2 p-value p-value PB-FEV1% pred ACO vs asthma −1.09 −1.3 −0.87 <0.001 91% 0.357 0.295 28 7 , 9 , 10 , 18–20 , 22 , 24 , 26 , 27 , 29–33 , 36 , 37 , 39 , 41 , 44–47 , 50 , 51 , 53 , 58 , 61 ACO vs COPD 0.15 0.05 0.26 0.004 80% 0.157 0.6 40 7–10 , 18 , 20–29 , 31–36 , 38–43 , 47 , 49–57 , 59–61 DLCO% pred ACO vs asthma −0.83 −1.24 −0.42 <0.001 89% 0.166 0.536 …”
Section: Resultsmentioning
confidence: 99%
“…In this issue, Tamura et al . 4 investigated the prevalence of mucus plugs using HRCT in patients with asthma, COPD, and asthma-COPD overlap (ACO). In addition, authors assessed the relationship between mucus plugs and the parameters of conventional spirometry or small airway dysfunction (SAD) in patients with airway diseases mentioned above.…”
mentioning
confidence: 99%
“…Tamura et al . 4 also assessed SAD using FVC and Fres and reported that SAD rather than large airway dysfunction was associated with mucus plugging in all the 3 obstructive airway diseases. Among several physiological measurements of SAD, FVC depends on patients’ efforts and thus shows a lack of reproducibility.…”
mentioning
confidence: 99%